Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, February 12, 1930 - Hawley, Joseph Roswell (The Hartford Times, Inc., 1930)
Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, February 12, 1930. Hawley was busy in congress while the republican national convention of 1880 was in session and after adjournment he was obliged to go to England on private business. So, he wrote a letter to the Courant from New York on June 18 which was published in lieu of an address he might have made at a ratification meeting for Garfield and Arthur in Hartford. July found him in London, and from there, he wrote to Warner.
1 electronic record. Scanned newspaper article. 1 image scans. 882 KB (903,426 bytes). 2 PDF copies (Master: PDF/A fmt/477; Access: reduced sized PDF fmt/19). 20.2 MB (21,210,022 bytes).
Keywords: Hawley, Joseph R. (Joseph Roswell), 1826-1905; American Civil War (United States : 1861-1865); United States--History--Civil War, 1861-1865; Personal correspondence; Letters; Newspapers